2003
DOI: 10.1046/j.1365-2885.2003.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intramammary treatment with procaine penicillin G vs. procaine penicillin G plus neomycin in bovine clinical mastitis caused by penicillin‐susceptible, gram‐positive bacteria – a double blind field study

Abstract: The efficacy of intramammary treatments containing procaine penicillin G alone (treatment A) or a combination of procaine penicillin G and neomycin (treatment B) was compared in treating clinical bovine mastitis caused by gram-positive bacteria susceptible in vitro to penicillin G. Both treatments were supplemented with a single intramuscular injection of procaine penicillin G on the first day of treatment. The study was carried out using a double blind design on commercial dairy farms in Southern Finland. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 12 publications
2
23
0
5
Order By: Relevance
“…In this study, the efficacy of IMIs in lactating cows have shown better due to the proper infusion of IMM tube at every 12 hours interval on affected quarter and maintain udder hygienic environment. The combinations of penicillin and aminoglycosides have shown a better efficacy for SCM in cows (Taponen et al, 2002). Owens and Nickerson (2001) showed similar result with cephapirin benzathine, penicillin-streptomycin, penicillin-novobiocin and tilmicosin infused intramammary infection in lactating cows for SCM.…”
Section: Efficacy Of Intramammary Infusion In Lactating Cowsmentioning
confidence: 54%
“…In this study, the efficacy of IMIs in lactating cows have shown better due to the proper infusion of IMM tube at every 12 hours interval on affected quarter and maintain udder hygienic environment. The combinations of penicillin and aminoglycosides have shown a better efficacy for SCM in cows (Taponen et al, 2002). Owens and Nickerson (2001) showed similar result with cephapirin benzathine, penicillin-streptomycin, penicillin-novobiocin and tilmicosin infused intramammary infection in lactating cows for SCM.…”
Section: Efficacy Of Intramammary Infusion In Lactating Cowsmentioning
confidence: 54%
“…Several studies have shown that the correlation between the antimicrobial susceptibility of S. aureus isolates determined in vitro and the actual bacteriological cure rate after antimicrobial treatment is only moderate (Pyorala and Pyorala 1998;Sol et al 1997Sol et al , 2000Wilson et al 1999). These epidemiological and clinical studies also revealed that treatment of older cows, or cows with high somatic cell counts (SCCs) in general is less successful and that treatment of cows with a high SCC due to a chronic infection often fails entirely (Apparao et al 2009;Barkema et al 2006;Owens et al 1997;Taponen et al 2003;Wilson et al 1999).…”
Section: Therapy Of S Aureus Mastitismentioning
confidence: 99%
“…Assim, apesar da base teórica para o uso destas ser a ampliação de espectro e a ação sinérgica contra certos microrganismos, alguns autores argumentam que, não foi devidamente comprovada em protocolos clínicos de tratamento de mastite bovina, a superioridade da formulação betalactâmicos associados aos aminoglicosídeos (TAPONEN et al, 2003). Nos Estados Unidos as associações deste tipo foram retiradas do mercado há alguns anos, devido às restrições impostas pela Food and Drug Administration.…”
Section: Resultsunclassified
“…Em relação ao uso de associações, vários estudos foram conduzidos em protocolos de campo com penicilinas no tratamento de mastite clinica e subclinica, comparando com associação de penicilinas e aminoglicosídeos, nenhum desses estudos demonstrou qualquer vantagem da associação sobre o uso do betalactâmico isoladamente (PYÖRÄLÄ; SYVAJARVI, 1987;JARP et al, 1989;MCDOUGALL, 1998;TAPONEN et al, 2003).…”
Section: Resíduos De Antimicrobianos No Leiteunclassified
See 1 more Smart Citation